MotionBlocks: Modular Geometric Motion Remapping for More Accessible Upper Body Movement in Virtual Reality - Wentzel, Johann; Luz, Alessandra; Mott, Martez; Vogel, Daniel (CHI 2025, 2025)
Movement-based spatial interaction in VR can present significant challenges for people with limited mobility, particularly due to the mismatch between the upper body motion a VR app requires and the user's capabilities. We describe MotionBlocks, an approach which enables 3D spatial input with smaller motions or simpler input devices using modular geometric motion remapping. A formative study identifies common accessibility issues within VR motion design, and informs a design language of VR motions that fall within simple geometric primitives. These 3D primitives enable collapsing spatial or non-spatial input into a normalized input vector, which is then expanded into a second 3D primitive representing larger, more complex 3D motions. An evaluation with people with mobility limitations found that using geometric primitives for highly customized upper body input remapping reduced physical workload, temporal workload, and perceived effort.